2010
DOI: 10.1007/s11104-010-0597-6
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse gas fluxes respond to different N fertilizer types due to altered plant-soil-microbe interactions

Abstract: The application of inorganic nitrogen (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 69 publications
0
20
0
2
Order By: Relevance
“…Both of them are strongly affected by N-fertilizer in agricultural system [42], with a major responsibility of agriculture for methane (CH 4 ) and nitrous oxide (N 2 O) emissions [43,44].…”
Section: Greenhouse Gas (Ghg) Emissions In Grazed Pasture Under N-fermentioning
confidence: 99%
See 1 more Smart Citation
“…Both of them are strongly affected by N-fertilizer in agricultural system [42], with a major responsibility of agriculture for methane (CH 4 ) and nitrous oxide (N 2 O) emissions [43,44].…”
Section: Greenhouse Gas (Ghg) Emissions In Grazed Pasture Under N-fermentioning
confidence: 99%
“…Nitrous oxide emission in grazed pasture is associated with animal stocking rate, animal excreta (urine and dungs), content of soil NO 3 -N, N-fertilizer rates, tillage, soil moisture, soil compaction, and other process that affect soil aeration [7,42].…”
Section: Greenhouse Gas (Ghg) Emissions In Grazed Pasture Under N-fermentioning
confidence: 99%
“…The tidal marshes are highly productive coastal wetlands, which can provide many important ecosystem services, such as storm protection for coastal cities, nutrient removal and carbon sequestration (Deegan et al, 2012). Increasing N loading may have strong effects on CH 4 emissions from the estuarine environments by influencing plant growth , changing the biological and chemical properties of soils (Min et al, 2011), stimulating the microbial processes (Blagodatskaya et al, 2007;Inselsbacher et al, 2011). Zhang et al (2010) studied the CH 4 emissions in the Wanggang coastal marsh and found that exogenous N addition dramatically stimulated CH 4 emission from the Spartina alterniflora mesocosm, and the effect of N addition on CH 4 emission from the native Suaeda salsa mesocosm was not significant.…”
Section: Introductionmentioning
confidence: 99%
“…무 경운 농법을 실시할 경우 경운 농법에 비해 친환경적인 동시 에 경제적이다 (Chapuis-Lardy et al, 2007;Inselsbacher et al, 2011;Keren et al, 1993;Xinhua et al, 2004;Yusuf et al, 1999). 무경운 재배에 대한 전 세계적인 관심 이 확산되고 있다.…”
unclassified